ETHNOGRAPHIC RESEARCH IN EDUCATION, RELIGION AND CULTURE - NEELAYOTHIN, AKKHARADET (Journal of Humanities and Social Sciences Mahamakut Buddhist University Isan Campus, 2025)
Ethnographic Research in Education, Religion and Culture is a qualitative research method aimed at studying and understanding the culture, beliefs, values, and ways of life of people in society, particularly in the contexts of education, religion, and culture. This research approach is rooted in anthropology and sociology, emphasizing the understanding of social phenomena through the emic perspective, or the insider’s viewpoint. It employs methods such as participant observation, in-depth interviews, and close interaction with the studied group. The research process consists of key steps: defining the research problem, designing the research, data collection, data analysis, and report writing. Ethnographic research is significant in uncovering the complex dimensions of culture and religion, helping us to understand social processes such as the transmission of religious knowledge, cultural changes, and the adaptation of groups in a transforming society. Furthermore, it plays a crucial role in promoting mutual understanding and respect among people with different beliefs and cultures, which is essential for building a harmonious and peaceful multicultural society.